2023
DOI: 10.3390/su15118692
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic Benefits for a Pig Farm and Local Bioeconomy Development from Extended Green Biorefinery Value Chains

James Gaffey,
Cathal O’Donovan,
Declan Murphy
et al.

Abstract: As the global population rises, agriculture and industry are under increasing pressure to become more sustainable in meeting this growing demand, while minimizing impacts on global emissions, land use change, and biodiversity. The development of efficient and symbiotic local bioeconomies can help to respond to this challenge by using land, resources, and side streams in efficient ways tailored to the needs of different regions. Green biorefineries offer a unique opportunity for regions with abundant grasslands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Previous work from [70] has highlighted the potential for press cake to replace silage in dairy cow diets, achieving comparable milk yields, while offering a reduction in nutrient (nitrogen and phosphorus) excrement losses and delivering a higher nitrogen use efficiency. Work by [71,72] has shown that the extracted protein LPC can serve as a suitable replacement for imported soya bean meal in the diets of pigs. By creating "off-farm" products, the biorefinery approach can help the farm to achieve further environmental benefits by enabling a redistribution of the environmental impacts associated with grassland production.…”
Section: Opportunities For Further Emission Reductionmentioning
confidence: 99%
“…Previous work from [70] has highlighted the potential for press cake to replace silage in dairy cow diets, achieving comparable milk yields, while offering a reduction in nutrient (nitrogen and phosphorus) excrement losses and delivering a higher nitrogen use efficiency. Work by [71,72] has shown that the extracted protein LPC can serve as a suitable replacement for imported soya bean meal in the diets of pigs. By creating "off-farm" products, the biorefinery approach can help the farm to achieve further environmental benefits by enabling a redistribution of the environmental impacts associated with grassland production.…”
Section: Opportunities For Further Emission Reductionmentioning
confidence: 99%
“…CBE is described as the interaction between bioeconomy and circular economy with the goal of producing bio-based goods, utilizing organic waste, and lowering GHG emissions [11,12]. CBE has been proposed as a promising solution to GHG emissions reduction within the wider agricultural and livestock sectors, while also providing new business and innovation opportunities in traditional primary production [13].…”
Section: Introductionmentioning
confidence: 99%